Phytotoxicity of Salvinia molesta in Diesel Exposure - Al-Baldawi, Israa Abdulwahab; Sheikh Abdullah, Siti Rozaimah; Ismail, Nur’ Izzati; Almanso, Asia Fadhile; Jasim, Salwa Shamran (Al-Khwarizmi Engineering Journal, 2021)
Phytoremediation is one of the methods to remove various types of pollutants from water and soil using plants. Salvinia molesta, an aquatic plant, is chosen in this study to determine its ability to degrade diesel as the pollutant in synthetic wastewater with different diesel concentrations (0, 8,700, 17,400, and 26,100 mg/L) for 14 days. Total petroleum hydrocarbon (TPH) has been used as an indicator to represent diesel concentration variation in wastewater. Degradation of TPH was 85.1% for diesel concentration of 8,700 mg/L, compared with only 53.9% in the corresponding control without plant. While, acute toxicity on S. molesta exposed in diesel concentrations of 17,400 and 26,100 mg/L was observed and eventually had caused the plants to die after 14 days of exposure. Additionally, throughout the phytotoxicity test, the biomass of S. molesta was found to fluctuate confirming inhibition on plant to survive with diesel contaminated water compared with the corresponding control without contaminant. Based on the results obtained it is suggested to decrease diesel concentration less than 8,700 mg/L in future study due to insolubility of diesel in water and the toxicity to the aquatic plants